Immunogenicity and safety study of 23-valent pneumococcal polysaccharide vaccine revaccination among elderly individuals aged 60–70 years in Shanghai, China - Qiu, Jing; Li, Zhi; Huang, Fang; Huang, Zhuoying; Liang, Xiufang; Li, Juan; Liao, Yuting; Guo, Xiang; Sun, Xiaodong (Frontiers in Immunology, 2025)
BackgroundTo understand the immunogenicity and safety of the 23-valent pneumococcal polysaccharide vaccine in elderly individuals aged 60–70 years in Shanghai after revaccination.MethodsA total of 330 elderly people aged 60–70 years were recruited to study the immunogenicity and safety of PPSV23 revaccination. The group with a history of PPSV23 vaccination and an interval of 5 years or more was selected as the revaccination group (n=220), and the group without any pneumococcal vaccine was selected as the first vaccination group (n=110).ResultsIn terms of immunogenicity, the GMCs of all serotypes before and after immunization were 1.15-21.57 µg/ml and 1.62-33.19 µg/ml, respectively, in the revaccination group, and the GMCs of all serotypes after immunization were higher than those before immunization (P<0.0001). After immunization, the total GMI of antibodies in the revaccination group was lower than that in the first vaccination group [1.62(1.57, 1.67) vs 3.20(2.82, 3.57), P<0.0001], and the GMIs of all serotypes in the revaccination group were also lower than those in the first vaccination group [(1.40-1.92) vs (1.82-4.69), P<0.0001]. In terms of safety, no serious adverse events occurred during the study and all adverse events that occurred were mild or self-limiting. From 0–30 days after immunization, 7 patients in the revaccination group and 14 patients in the first vaccination group experienced adverse events, with incidence rates of 3.18% and 12.73%, respectively, which were lower in the revaccination group than in the first vaccination group (P=0.0008).ConclusionsCompared with those before vaccination, the antibody levels of elderly people aged 60–70 years in Shanghai who were inoculated with PPSV23 for 5 years or more tended to increase but were lower than those in the first vaccination group. The safety of revaccination with PPSV23 was favorable.Clinical Trial Registrationhttp://www.chictr.org.cn, identifier ChiCTR2100042000; http://clinicaltrials.gov, identifier NCT04701788.